PERLINDUNGAN HUKUM PIDANA TERHADAP KORBAN LAYANAN PINJAM MEMINJAM BEBASIS TEKNOLOGI DI INDONESIA - M. Imam Indra; Erdianto Effendi; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The development of fintech is very significant in Indonesia, so there is aspecial concern regarding legal protection for its users because this is becausethere is no special regulation that regulates fintech itself, both in the form ofprotection of privacy and data privacy of users who register themselves on onlineplatforms. So that in practice it triggers the emergence of various criminal acts inthe form of fraud, extortion, and so on which have the potential to cause verylarge losses. And criminal acts that occur are regulated by law. Based on themain idea above, several problems can be formulated, namely how is theprotection of criminal law for victims of technology-based lending and borrowingservices in Indonesia and what are the types of criminal acts of technology-basedlending and borrowing services in Indonesia.The writing of this thesis uses normative legal research methods withlibrary research data collection, namely by researching library materials orsecondary data in the form of primary legal materials, namely relatedregulations, secondary legal materials, namely related documents and tertiarylegal materials. which is a guide to primary and secondary legal materials orresearch on legal systematics. The secondary data that has been compiled is thenanalyzed using qualitative methods to obtain results or conclusions, namely byapplying the law in accordance with the criminal act experienced such as thedistribution of personal data as regulated in Article 32 in conjunction with Article48 of the ITE Law, threats regulated in Article 365 of the Criminal Code andArticle 29 in conjunction with Article 45 of the ITE Law and other criminal acts.Keywords: Fintech, Legal Protection, Lending Services, Technology